Microdilution Susceptibility Testing of Amphotericin B, Itraconazole, and Voriconazole against Clinical Isolates of Aspergillus and Fusarium Species - Arikan, Sevtap (American Society for Microbiology, 1999)
We compared the activities of amphotericin B, itraconazole, and voriconazole against clinical Aspergillus (n = 82) and Fusarium (n = 22) isolates by a microdilution method adopted from the National Committee for Clinical Laboratory Standards (NCCLS-M27A). RPMI 1640 (RPMI), RPMI 1640 supplemented to 2% glucose (RPMI-2), and antibiotic medium 3 supplemented to 2% glucose (AM3) were used as test media. MICs were determined after 24, 48, and 72 h. A narrow range of amphotericin B MICs was observed for Aspergillus isolates, with minor variations among species. MICs for Fusarium isolates were higher than those for Aspergillus isolates. MICs of itraconazole were prominently high for two previously defined itraconazole-resistant Aspergillus fumigatus isolates and Fusarium solani. Voriconazole showed good in vitro activity against itraconazole-resistant isolates, but the MICs of voriconazole for F. solani were high. RPMI was the most efficient medium for detection of itraconazole-resistant isolates, followed by RPMI-2. While the significance remains unclear, AM3 lowered the MICs, particularly those of amphotericin B.